PENGARUH KECERDASAN EMOSIONAL TERHADAP PENYESUAIAN DIRI DAN PENGAMBILAN KEPUTUSAN PADA PERSONEL DITSAMAPTA POLDA KEPULAUAN RIAU DALAM MENGHADAPI SITUASI KRISIS - Rahmini Ariyanti; Ully Crenilia; Rini Sugiarti; Fendy Suhariadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The police profession is one of the professions that faces great challenges in crisis situations. Police members are required to make the right decisions and adapt to stressful conditions quickly and effectively. This study aims to analyze the influence of emotional intelligence on decision-making and self-adjustment in police members who serve in operational functions. The research method used is a correlational quantitative approach with data collection through questionnaires distributed to 100 personnel of the Riau Islands Police Directorate. Emotional intelligence is measured based on five dimensions: self-awareness, self-management, motivation, empathy, and social skills. Decision-making and self-adjustment are measured using a standardized scale that has been validated. The results of the study show that emotional intelligence has a significant influence on decision-making and self-adjustment of police members. The dimensions of self-management and empathy contribute the most in supporting quick and rational decision-making skills, while self-awareness plays an important role in self-adjustment to crisis situations. These findings underscore the importance of developing emotional intelligence through training to improve the performance of police members, especially in dealing with stressful situations. This study concludes that emotional intelligence is a key factor that affects the effectiveness of decision-making and self-adjustment in police members. The practical implication of this study is the need to integrate emotional intelligence training in human resource development programs in police institutions.